2004
DOI: 10.1079/joh2004251
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, intensity and clinical signs of urinary schistosomiasis in Imo state, Nigeria

Abstract: Urine samples were assayed for urinary schistosomiasis in four local government areas (LGA) of Imo State, Nigeria between May 1998 and September 2000. A total of 3504 persons were sampled, with 880 (25.1%) being positive for urinary schistosomiasis, based on records of eggs of Schistosoma haematobium. The prevalence of S. haematobium infection differed in the various LGAs, with Oguta (38.9%) and Owerri-West (10.4%) showing the highest and the lowest values, respectively. Prevalence was higher in males (67.4%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
9
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
6
9
1
Order By: Relevance
“…A recently conducted study in two rural communities in the same area reported a similar prevalence of 47% (Oladejo & Ofoezie 2006), indicating that infection has remained unabated in this and, most likely, other dam regions of Nigeria. Age and sex-related prevalence and the intensity of infection in the present study were similar to those reported from other West African endemic foci (Okoli & Odaibo 1999, Mafe et al 2000, Okoli & Iwuala 2004, Oladejo & Ofoezie 2006.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A recently conducted study in two rural communities in the same area reported a similar prevalence of 47% (Oladejo & Ofoezie 2006), indicating that infection has remained unabated in this and, most likely, other dam regions of Nigeria. Age and sex-related prevalence and the intensity of infection in the present study were similar to those reported from other West African endemic foci (Okoli & Odaibo 1999, Mafe et al 2000, Okoli & Iwuala 2004, Oladejo & Ofoezie 2006.…”
Section: Discussionsupporting
confidence: 90%
“…The predominant species in this country is Schistosoma haematobium, which most commonly presents with haematuria, suprapubic pain and pain while urinating (Okoli & Iwuala 2004).…”
mentioning
confidence: 99%
“…Studies in Nigeria among school aged children in various parts of the country and in both rural and urban environments have shown that S. haematobium is clearly a problem of this age group. Prevalence among school aged children ranges from 20-40 % in typical communities 4,5 , but can be as high as 50-70 % in areas where environmental changes occur due to constructions such as human-made dams and quarries 6,7 . In Ogun and Lagos State, urinary schistosomiasis has been reported in several communities [8][9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…This is explained by the reduction of exposure to contaminated water [10]. On the contrary females, besides being more infected, presented a pattern of infection highest in the intermediate age group (25-34).…”
mentioning
confidence: 99%